Autoimagem, repercussões sociais e pontos de apoio para usuários de substâncias psicoativas - Souto, Valquíria Toledo (2015)
The present study aimed to know how the guys who use psychoactive substances perceive their body image and analyze the social impact and the support points identified by the subjects that make use of psychoactive substances. It is an exploratory and descriptive research, with qualitative approach, developed by the use of problematizing methodology, with the application of the Arc by Charles Maguerez. 16 subjects participated in the research, who were under treatment in a Center of Psycho and Social Attention Alcohol and Drugs (Centro de Atenção Psicossocial Álcool e Drogas (CAPS AD), from a municipality of the countryside of the state of Rio Grande do Sul, Brazil. The production of the data research occurred between the months of April and June, 2014, through the performance of five reflexive meetings . The analysis of the data occurred in three phases: collection and organization; codification; and, identification of the emerging themes. Because it is a research with human beings, the ethical aspects were respected according to Resolution 466/12 of the National Council of Health. As results, we identified three emerging themes: the use of psychoactive substances and the reflexes about the self-image; the social echoes that evolve to be a user of psychoactive substances; and the points of support that potentialize the changes. We concluded that the self-image constructed by these subjects suffer influences of a life crossed by the experiences of use of psychoactive, echoing in feelings of not valuing themselves, problems with the self-esteem and self-care. They experience a social context full of prejudice, they are tagged, stigmatized, in such a way that they started to adopt the negative stereotypes for themselves. They demonstrate a hopeless attitude in front of possible changes in this scenario of discrimination and exclusion. Nevertheless, they find support to continue the treatment and to face the problems of the routine in CAPS AD, in the family and in faith. In this sense, we reiterate the importance of implantation/maintenance of spaces to demystify certain conceptions that amplify the social stigmatization of these subjects, and encourage that the users occupy the spaces of social participation in the fight for policies and practices that expand/ensure their condition of citizenship.